Implementation of Fuzzy Controller for Capacitor Voltage Balance in MMC for PV based Induction Motor Drive (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This paper discusses the capacitor voltage balance in MMC controlled by the space vector PWM technique. The proposed converter is included with four sub-modules each comprising a half-bridge converter with a DC link capacitor. An optimized control structure for capacitor voltage balance with the conventional PI controller is simulated compared to the updated visual system controller that changes the standard control. The converter function is analyzed with the comparison of settling times of the DC link capacitors voltages in each module. The performance of the induction motor is analyzed by connected to this converter generating speed and torque characteristic parameters. The architecture and analysis was performed using the MATLAB Simulink software, which uses the powergui function to create time-based graphs.